Using Objective and Subjective Measures of Neighborhood Greenness and Accessible Destinations for Understanding Walking Trips and BMI in Seattle, Washington - Tilt, Jenna H.; Unfried, Thomas M.; Roca, Belen (American journal of health promotion, 2007)
Purpose. Examine the influence of destinations within walking distance of a residence and vegetation on walking trips and body mass index (BMI). Design. Cross-sectional analysis of data from residences with varying accessibility and greenness. Setting. Seattle, Washington. Subjects. Stratified random sample of residents, stratified by accessibility and greenness. Response rate: 17.5%, 529 respondents. Measures. Accessibility and greenness were measured objectively by Geographic Information Systems (GIS) Network Analysis and normalized difference vegetation index (NDVI), respectively. Self-reported destinations, natural features, walking trips, BMI, and importance of destinations were measured through a postal survey. Results. Objective accessibility were related to walking trips per month (r2 = .110, p < .0001), as was subjective greenness (r2 = .051, p < .0001), although objective measures of actual greenness were not. In areas with high accessibility, BMI was lower in areas that had high NDVI, or more greenness (r2 = .129428, model p < .0001; t-test of interaction p = .0257). Low NDVI areas were associated with overestimation of the number of destinations within walking distance (F1, 499 = 11.009, p < .001). Conclusions. Objective and subjective measurements of accessibility and greenness led to an understanding of variation among walking trips and BMI in different neighborhoods.